'Everyone seems to be agreeing at the minute that face-to-face is the way forward': practitioners' perspectives on post-pandemic mathematics and statistics support. (6th October 2021) - Gilbert, Holly; Hodds, Mark; Lawson, Duncan
Abstract: Mathematics and statistics support (MSS) is now firmly embedded in the learning and teaching infra-structure of most UK universities and in many universities worldwide. In common with other higher education activities, in response to restrictions put in place to reduce the spread of Covid-19, MSS transitioned rapidly to online delivery in spring 2020. This paper reports on thinking within the practitioner community about good practice in the delivery of online MSS. A two-phase approach was used to collect this shared wisdom: an initial questionnaire in May 2020 (just after provision had moved online) and interviews with practitioners in January/February 2021 after colleagues had some experience in online provision and had had the opportunity to reflect on and modify the measures hastily put in place in spring 2020. The focus of the study is not only on what is currently being provided but also on what MSS will look like once all pandemic related restrictions have been ended. The overall feeling of the participants is that face-to-face MSS will return as the dominant form of delivery but that the benefits of online provision are such that a significant minority of provision will remain in this form.